THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND ATTITUDE OF MOTHERS OF CHILDBEARING AGE COUPLES TOWARDS THE USE OF CONTRACEPTIVES AT THE KALANGANYAR HEALTH CENTER, LEBAK REGENCY IN 2023 - Andriyani, Rini; Yuliani, Indah (HEARTY, 2025)
Background: Based on the results of a preliminary study conducted at the Kalanganyar Health Center, Lebak Regency, it was found that 8 out of 10 mothers of couples of childbearing age (80%) did not know the benefits, types and side effects of the contraceptives used. Purpose: To determine the relationship between the level of knowledge and attitudes of mothers of childbearing age couples towards the use of contraceptives at the Kalanganyar Health Center, Lebak Regency. Methods: Cross sectional through a point time approach where samples are taken using a total sampling of 75 respondents. Data analysis using chi square test. Results: Demonstrate the level of knowledge and attitudes associated with contraceptive use (p-value 0,000). Conclusion: There is a relationship between the level of knowledge and the attitude of mothers of childbearing age couples towards the use of contraceptives. It is expected that the Kalanganyar Health Center through the Village Midwife will provide counseling and consultation guidance on the use of contraceptives so that mothers of childbearing age couples have awareness of the importance of using contraceptives.